Are Tax Havens and Offshore Financial Centers Cracked Down On? A Study on the International Standard of Exchange of Information on Request - Li, Yijun; Ma, Mark (Shuai) (The Accounting Review, 2022)
ABSTRACT To “crack down” on tax havens and offshore financial centers, the Organisation for Economic Co-operation and Development (OECD) has promoted an internationally agreed tax standard of exchange of information on request since 2009. Using a difference-in-differences analysis, we find that the implementation of the standard significantly reduces aggressive tax avoidance by affected U.S. multinational firms with material subsidiaries in tax havens and other offshore financial centers. The effects are stronger when firms have more incentives and opportunities for income-shifting or when tax enforcement is stronger. Overall, our study helps the OECD and other regulators better understand the effect of the internationally agreed standard on corporate tax avoidance. Data Availability: All data are available at the source indicated.